THE EFFECT OF WORK FACILITIES, WORK ENVIRONMENT AND TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE FOR ENVIRONMENTAL AND FORESTRY SERVICE EMPLOYEES RIAU ISLANDS PROVINCE - Siregar, Haposan; Ngaliman, Ngaliman; Satriawan, Bambang; Indrayani, Indrayani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to examine the effect of work facilities, work environment and transformational leadership on organizational commitment through job satisfaction as an intervening variable for the employees of the Environment and Forestry Office of the Riau Islands Province. The sample used is 129 respondents from 129 employees. The sampling technique used is census. The method used in this study uses quantitative research and the type of research used is explanatory research or explanation. The data analysis method used is the structural equation model (SEM-PLS).Based on the data analysis, it was found that the direct effect of Work Facilities on Organizational Commitment was positive and not significant. The direct effect of work environment on organizational commitment is positive and significant. The direct effect of Transformational Leadership on Organizational Commitment is negative and insignificant. The direct effect of Job Facilities on Job Satisfaction is positive and not significant. The direct effect of the work environment on job satisfaction is positive and significant. The direct effect of Transformational Leadership on Job Satisfaction is positive and significant. The direct effect of job satisfaction on organizational commitment is positive and significant. The indirect effect between Work Facilities on Organizational Commitment and Job Satisfaction as an intervening variable is positive and not significant. The indirect effect between Work Environment on Organizational Commitment and Job Satisfaction as an intervening variable is positive and significant. The indirect effect between Transformational Leadership on Organizational Commitment and Job Satisfaction as an intervening variable is positive and significant.